THE INFLUENCE OF ARTIFICIAL INTELLIGENCE IN THE MEDIA INDUSTRY IN INDONESIA - Masriadi, Masriadi; Bahri, Halida (Program Studi Sosiologi Universitas Malikussaleh, 2024)
The influence and use of Artificial Intelligence (AI) in the mass media industry in Indonesia has begun to be applied. Both online media and television. In fact, mass media in Indonesia also produce content in the form of audio, video, text and presenters using AI. The use of this technology does make it easier for media workers. However, it has various shortcomings and problems that arise as a logical consequence of the presence of AI technology. This research was conducted using a qualitative approach with a descriptive analysis style. The results show that AI technology has shortcomings in terms of accuracy, verification, and validation of data collected from the digital universe. On the other hand, it has no legal justification in Indonesia. For this reason, special regulations for the use of AI in the Indonesian mass media are needed. Thus, the public as the main recipient of information is not harmed and maintains the image of the media industry as the most trusted institution in the country.